FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENYERAPAN ANGGARAN DI BALAI BESAR KONSERVASI SDA JAWA BARAT - Winna Roswinna; Annisa Fitri Anggraeni; Deden Komar Priatna; Nancy Monalisa; Roby Ahada (Value : Jurnal Manajemen dan Akuntansi, 2023)
The State Revenue and Expenditure Budget as an acceleration of budget implementation is needed to support sustainable national development programs by optimizing the role of state revenues and expenditures, especially Ministry/Institution revenue and spending on economic growth each year. A good understanding of the mechanisms for compiling Ministry/Institution budgets is very important to be understood by various parties, especially in the framework of achieving optimal work unit goals and functions. The aim of the study was to find out the condition of stakeholder participation in budgeting, the budget revision process and how these factors affect the effectiveness of budget spending at the West Java Natural Resources Conservation Center (BKSDA). The research methodology is descriptive quantitative using primary data collected from users of the West Java Province BKSDA budget for the period 2019 to 2021. The data collection method is questionnaire interviews. The results of the study show that some budgetary participation has a significant effect on the effectiveness of budget absorption, but partial budget revisions have no significant effect on the effectiveness of budget spending. Meanwhile, simultaneous budget participation and budget revision affect the effectiveness of budget absorption. The policy of participation in budget preparation and budget revision needs to be further enhanced by the BKSDA of West Java Province so that the achievement of the effectiveness of budget absorption can be more optimal Keyword: Participation, Revision, Budget Absorption Effectiveness